Badminton Stroke Skill Levels in Children Aged 10-12 Years at Kaisar Badminton Club Tegal Regency - Ardyanto, Sofyan (Indonesian Journal of Sport Management, 2024)
This study aimed to assess the badminton stroke skill levels of children aged 10-12 years at the Kaisar Badminton Club in Tegal Regency. The study employed a cross-sectional design, where 120 children were randomly selected and evaluated based on their proficiency in forehand, backhand, and smash strokes. The results showed that the children demonstrated varying proficiency levels in each stroke, with the most dominant forehand stroke. The findings suggest that the children at the Kaisar Badminton Club require targeted training to improve their backhand and smash strokes. The study's results can inform the development of effective training programs to enhance the overall badminton skills of children in the region.